R&D and productivity in German manufacturing firms - Dietmar Harhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
This paper uses a new firm panel data set to explore the relationship between R&D and productivity in German manufacturing firms for the period from 1979 to 1989. The results confirm the view that R&D is an important determinant of productivity growth. In the cross-section, the elasticity of sales with respect to R&D capital is on the order of 14 per cent. Using fixed-effects estimators yields R&D elasticities of about 8 per cent. Differencing estimates improve considerably when growth rates are computed over longer time periods, suggesting that the divergence between time-series and cross-sectional estimates is driven by measurement errors. The paper also considers differences between high-technology and other firms. Cross-section and panel elasticity estimates of the R&D effect diverge considerably for the two groups, while the corresponding rate of return estimators display far less variation. There is some evidence that the R&D elasticity increased during the early 80s, and that it fell sharply back to its 1979 value during the period from 1985 to 1989.
Keywords: 330